Context-based sales and operations planning (S&OP) research: A literature review and future agenda. Issue 1 (12th February 2018) - Kristensen, Jesper; Jonsson, Patrik
Abstract : Purpose: The purpose of this paper is to describe and categorise how current literature contributes to sales and operations planning (S&OP) research on how contextual variables affect S&OP design and to frame future areas for context-based S&OP research. Design/methodology/approach: The method used was a systematic literature review. Studies for review were obtained through a keyword search of five relevant databases, manual searches of relevant journals and snowballing of citations in relevant papers. In total, 571 papers published between 2000 and 2017 were assessed, and 68 papers were included in the review. Findings: The review found that S&OP design depends on industry, dynamic complexity, detail complexity and organisational characteristics. The findings of the literature review suggest that future research should study the roles of industry, complexity, system and process and organisational characteristics in S&OP design. Research limitations/implications: The findings revealed several gaps in the literature on context-dependent S&OP design. To address these gaps, an agenda for future S&OP contingency research is developed. Practical implications: The findings revealed which contextual areas and specific S&OP design issues must be considered when designing and implementing S&OP. Originality/value: This study focussed on identifying relevant research on S&OP design by analysing the contribution of literature to a research framework inspired by contingency-based research of operations and supply chain management.